(untitled) (Journal of Economic Research & Business Administration, 2015)
This article is about economic relation between Kazakhstan and Germany. In this research is considered the most important topic of economic. That is cooperation between Germany and Kazakhstan, that unchanged state priority is. Development of partnerships with all countries is noted in forward-looking Strategy «Kazakhstan-2050».